Pengaruh Iklim Organisasi Terhadap Produktivitas Kerja Pegawai Di Sekretariat Daerah Kota Bandung - Rasino, Rasino; Alhadihaq, M Yusuf; Sumiati, Nia (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The purpose of this research is to examine the simultaneous and partial influence of organizational climate on employee work productivity. The organizational climate studied includes the dimensions of structure, communication flow, responsibility, respect for human resources as well as rewards and sanctions. The sample is employee staff who are registered as Civil Servants totaling 128 people spread across 8 sections. The data collection instrument used was a questionnaire using a Likert scale. The data obtained were analyzed using simple linear regression analysis. The results of the study stated that there was an influence of organizational climate on the work productivity of employees at the Regional Secretariat of the City of Bandung. The simultaneous influence of organizational climate on employee work productivity is 54.3%.